Fat mass and obesity associated gene variants are associated with increased growth hormone levels and affect glucose and lipid metabolism in lean women - Lukášová, P; Vaňková, M; Včelák, J; Vejražková, D; Bradnová, O; Stanická, S; Hainer, V; Bendlová, B (Physiological research, 2015)
First intron variability of the fat mass and obesity associated gene (FTO) has strong impact on adiposity. We focused on lean women carrying the most "obesity-risk" haplotype to study their anthropometric parameters and hormonal and metabolic profile. Genotype-phenotype correlation was performed in a group of 172 lean women (body mass index (BMI) >/=18.5 and 25 kg/m(2); age 26.8+/-7.26 years), 77 of them used hormonal contraceptives. Even in lean women the association of the risk haplotype CAGA with BMI was confirmed but it did not influence the anthropometric indices of body composition. CAGA carriers compared to non-carriers had significantly higher both fasting (p=0.016) and post glucose load (p<0.001) levels of growth hormone (GH), significantly higher glucose, insulin and C-peptide levels in the late phase of oGTT and lower fasting concentration of total cholesterol and LDL-cholesterol. Administration of hormonal contraceptives further increased observed hormonal and metabolic effects in CAGA carriers. We conclude that higher levels of GH in lean women carrying the FTO "obesity risk" haplotype could protect them from the development of obesity. The relation between the FTO gene variability and GH secretion has to be elucidated. This is the first study demonstrating the interaction of FTO genotype with hormonal contraception.
Keywords: dospělí; Female; Adult; ženské pohlaví; mladý dospělý; Obesity; hubenost; Human Growth Hormone; lidé; Thinness; Lipid Metabolism; Adiposity; adipozita; lidský růstový hormon; Proteins; metabolismus lipidů; kohortové studie; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Genetic Variation; Cohort Studies; proteiny; obezita; glukosa; Young Adult; Glucose; index tělesné hmotnosti; gen pro FTO; Body Mass Index; genetická variace; Humans